A study on the significant Factors affecting the popularity of ATM cards the case of UPV-CM - Gatinao, Rosalyn; Genoves, Gina; Gumban, Aileen; Limsiaco, Ma. Liza; Turija, Janine Emmylou
In undertaking this study, the researchers assumed that the benefits received and the problems encountered by the subscribers affect the popularity of the use of ATM cards, specifically the ATM cards of Megalink, Bancnet and Expressnet. The study seeks to answer the question " what are the significant factors affecting the popularity of ATM cards among UPV-students?" The researchers conducted a survey employing purposive sampling method on students enrolled in UPV-CM. A total of 100 or 37.14% respondents were taken from a sample size of 285. Considering the large number of the sample size, the researchers decided to get only 100 respondents as the subject of the study. Findings and results showed that convenience, easy access to funds, easy transfer of funds, card captured by machine, and machine cannot readily process transaction are the significant factors that highly affect the popularity of the use of ATM cards. While the significant factors that affect its popularity are more access to different banks and risk of theft from account.